PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI ENTITAS MIKRO KECIL MENENGAH (SAK EMKM) BAGI PT. SENTRA TRANS PAPUA - Wonar, Klara; Salle, Hesty Theresia; Salle, Agustinus; Allo Layuk, Paulus Kombo (Jurnal Abdimas Bina Bangsa, 2024)
The report preparation training aims to provide material related to the benefits and types of financial statements, train MSME actors in preparing profit and loss statements, train MSME actors in preparing financial position reports and train MSME actors in preparing capital change reports. The methods used during service activities are lectures, training and evaluation